High protein diet attenuates histopathologic organ damage and vascular leakage in transgenic murine model of sickle cell anemia. (August 2014) - Manci, Elizabeth Ann; Hyacinth, Hyacinth I; Capers, Patrice L; Archer, David R; Pitts, Sydney; Ghosh, Samit; Patrickson, John; Titford, Michael E; Ofori-Acquah, Solomon F; Hibbert, Jacqueline M
Previous reports have shown that a high protein diet improves weight gain and decreases expression of inflammatory markers in weanling Berkeley transgenic sickle cell mice. The effect of this diet on the underlying histopathology, however, has not been studied. Age-matched, male C57BL/6 controls (n = 24), Berkley sickle mice (n = 31) and Townes sickle mice (n = 14) were randomized in a terminal experiment at weaning to isoenergetic diets, with either normal (20%) or high (35%) amount of energy from protein, by replacing dextrin. Tissue sampling for blinded histologic study and scoring of changes at baseline and after 3 months of feedings showed progressive siderosis and infarcts in spleen, kidney, and liver in all sickle groups, and no significant changes in age- and sex-matched normal controls. High-protein (35%) fed Berkeley sickle mice had significantly fewer (p < 0.01) infarcts in spleen (35.7% less), liver (12.5% less), and kidney (28.6% less) and lower histopathologic scores (p < 0.01) for chronic tissue injury in liver and spleen than matched normal-protein (20%) fed Berkeley sickle mice. In addition, high-protein fed Townes sickle mice had less vascular leakage (∼36%) in the heart, lungs, and brain and a better survival rate (21%) than matched normal-protein Townes sickle mice. This is the first report of histopathologic evidence that a high protein:calorie diet attenuates sickle cell related chronic organ injury in transgenic sickle cell mouse models.